Metropolitan Arrangements in the Philippines: Passing Fancy or the Future Megatrend - Rosario G. Manasan; Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
Associated with the country's drive to become more modern and competitive global economy is the emergence of metropolises, which is defined in theory as large urban settlement having at least one million population. Given such definitions, the only metropolises that would qualify are Metro Manila, Metro Cebu and Metro Davao. There are, however, other metropolises that do not qualify to the theoretical standards but behave functionally as such and are henceforth classified as metropolitan arrangement. Its emergence, whether fleeting or a prelude to the future trend, is the main concern of this paper. The paper also examines whether there are significant benefits to this form of geopolitical cooperation and how this can be strengthened and enhanced as an alternative mechanism for efficient delivery of urban service.
Keywords: 330; urban management; urbanization; metropolitan structure; metropolitan planning and development